Assessing the distinctiveness of phonological features in word recognition: Prelexical and lexical influences. (May 2017) - Martin, Alexander; Peperkamp, Sharon
Highlights: A discrimination task is used to test the perceptual salience of phoneme contrasts. Manner contrasts in French are easier to discriminate than place or voicing ones. A new measure of functional load is proposed focusing on phonological features. In French nouns, place has a higher functional load than voicing and manner. During word recognition, bottom-up perceptual and top-down lexical biases coalesce. Abstract: Phonological features have been shown to differ from one another in their perceptual weight during word recognition. Here, we examine two possible sources of these asymmetries: bottom-up acoustic perception (some featural contrasts are acoustically more different than others), and top-down lexical knowledge (some contrasts are used more to distinguish words in the lexicon). We focus on French nouns, in which voicing mispronunciations are perceived as closer to canonical pronunciations than both place and manner mispronunciations, indicating that voicing is less important than place and manner for distinguishing words from one another. We find that this result can be accounted for by coalescing the two sources of bias. First, using a prelexical discrimination paradigm, we show that manner contrasts have the highest baseline perceptual salience, while there is no difference between place and voicing. Second, using a novel method to compute the functional load of phonological features, we show that the place feature is most often recruited to distinguish nouns in the French lexicon, while voicing and manner are exploited equally often.